First experience of a hemophilia monitoring platform: florio HAEMO - Zapotocka, Ester; Batorova, Angelika; Bilic, Ernest; Boban, Ana; Escuriola Ettingshausen, Carmen; Faganel Kotnik, Barbara; Hrdlickova, Radomira; Laguna, Pawel; Machal, Jan; Nemes, Laszlo; Zupan, Irena Preloznik; Puras, Gediminas; et al. (Research and practice in thrombosis and haemostasis, 2022)
BACKGROUND: florio HAEMO is a new hemophilia treatment monitoring application consisting of a patient smartphone application (app) and a web-based dashboard for healthcare professionals, providing several novel features, including activity tracking, wearable connectivity, kids and caregiver mode, and real-time pharmacokinetic factor level estimation. OBJECTIVES: To assess intuitiveness, ease-of-use, and patient preference of florio HAEMO in Central Europe using a cross-sectional survey. METHODS: This survey was conducted in six Central European countries between 9 December 2020 and 24 May 2021. The online questionnaire included 17 questions about overall satisfaction, ease-of-use, intuitiveness, and patient preference. Adults or children with hemophilia on regular prophylaxis and using the florio HAEMO app for a minimum of 1 week were invited to complete the online questionnaire by their treating physician. RESULTS: Sixty-six participants took part in the survey. The median duration for all respondents using the florio HAEMO app was 3 to 4 weeks. Overall, 89.4% of users reported being very satisfied or rather satisfied after using florio HAEMO. Of the 23 respondents who had switched from another hemophilia app, 87.0% indicated that they strongly preferred or preferred using florio HAEMO. Most florio HAEMO users reported that the app was very easy or rather easy to use (97.0%) and intuitive (94.0%). florio HAEMO had a positive impact on daily living, with 78.8% of users reporting that the app was very important or rather important to them. CONCLUSIONS: This survey suggests that florio HAEMO is an easy-to-use and intuitive app to assist self-management of home prophylaxis.
Keywords: telemedicine; hemophilia; patient preference; pharmacokinetics